Physical literacy in older adults: a scoping review protocol - Galán-Arroyo, Carmen; de los Ríos-Calonge, Javier; Rojo-Ramos, Jorge; Parraca, Jose A.; Fonseca, Cesar; Castillo-Paredes, Antonio; da Silva Batista, Marco Alexandre (Frontiers in Public Health, 2024)
Population aging is a prominent phenomenon worldwide. The increase in physical inactivity and co-morbid diseases poses a major challenge to current community health policies. Physical activity guidelines recommended for older people have not been met by this population group. For this reason, a new model, physical literacy, is being innovated and has gained global attention and has emerged as an effective and innovative active aging strategy to improve physical activity participation of this vulnerable group. However, the evidence on physical literacy in the older adult so far is brief and diffuse. Therefore, the aim was to conduct a scoping review protocol to identify and map physical literacy in older people. This scoping review protocol was based on the Joanna Briggs Institute Method. The search will be performed on Embase, IBSS ProQuest, Medline OVID, PsycINFO Ebsco, PubMed, ScienceDirect, Scopus, SPORTDiscus, Social Services Abstracts ProQuest, Sociological Abstracts ProQuest, Web of Science ISI, Wiley Online Library, Cochrane Library, and ERIC Ebsco databases. All types of studies published since 2001 in English, Spanish, and Portuguese examining physical literacy over the lifespan of older adults were included. Two independent reviewers will organize and select studies according to the objectives and questions of the scoping review. The selected publications will be organized and summarized using a checklist proposed by the PRISMA-ScR. Qualitative data analysis (thematic analysis) will be performed to identify meanings and patterns to answer the research question. The final scoping review will present the main evidence available, key concepts/definitions, research conducted, and knowledge gaps related to physical literacy in older adults, leading to strategies to improve the community health of this population, as well as health literacy.